Analisis Hukum Pemberian Kredit kepada Usaha Kecil di Provinsi Sumatera Utara - Abi Jumroh Harahap (Universitas Negeri Medan, 2015)
For empowering economic of the people (small enterprises), the government has enacted some regulations to provide facilities including credit for enterpreneur even resolving the marketing problem such as Law No. 20 of 2008 on Micro, Small, and Medium Enterprises. This is a legal research of normative with the empirical approach based on the phenomenon in social field, then all of data is displayed systematically to be analyzed deductively. The population consists of 32 regency/city located in the North Sumatra Province, but sample is selected purposively namely five regency/city of them. Duration of the research is 2 years which is oriented on: to improve the policy of government considering small enterprises empowerment in Indonesia spesifically in North Sumatra, scientific publication in a local journal having international serial number (ISSN) or national acredited journal and textbook or handbook. Financial limitedness for developing micro, small and medium enterprises (UMKM) is the clasical problem found frequently in the developing countries. This effects to level of production and its development. The public grants provided by government for developing UMKM is distributed through the special financial agencies such as the bank for industrial development and agribusiness. The commercial banks are hoped to be able to participate in the sector by quota of credit, subsidy, tax income, and guarantee for failure.